Judge's Considerations When Handing Down Marriage Dispensation Decisions in Aceh Singkil Regency for the 2019-2023 Period - Sulaeman AR; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (GoAcademica Research & Publishing, 2024)
This study aims to comprehensively examine the reality of the dynamics of marriage dispensation application cases at the Singkil Sharia Court, Aceh Singkil Regency, the judge's considerations in accepting or rejecting marriage dispensation applications, and the legal basis used by the judge in deciding marriage dispensation cases at the Singkil Sharia Court, Aceh Singkil Regency. This study uses a naturalistic qualitative approach with a field research method. Data collection techniques are carried out through observation, interviews, and documentation. This study is descriptive naturalistic, which aims to clearly and in detail describe the social reality at the Singkil Sharia Court, Aceh Singkil Regency. The results of the study indicate that the process of submitting a marriage dispensation application at the Singkil Sharia Court reflects the same requirements as the Supreme Court Regulation (Perma) No. 5 of 2019. The findings indicate that the main reasons for the application include parental concerns about indecent behavior, customary considerations and scheduling of wedding receptions, and premarital sexual relations. The judge's basis for deciding on a marriage dispensation application involves considerations such as the absence of parents in mediation, family pressure, and document inconsistencies. The judge's considerations in deciding on a marriage dispensation include the child's readiness to live in a household, psychological and financial capabilities, and approval from the extended family. This study emphasizes the importance of adjusting decisions to existing regulations to ensure fairness.